2022
DOI: 10.1002/ps.6781
|View full text |Cite
|
Sign up to set email alerts
|

Substitution or complementarity: why do rice farmers use a mix of biopesticides and chemical pesticides in China?

Abstract: BACKGROUND: Although scholars have become increasingly concerned about finding ways to encourage more farmers to use biopesticides and fewer to use chemical pesticides, few studies have investigated the prevalence of Chinese rice farmers' mixed use of biopesticides and chemical pesticides for pest management.RESULTS: Based on a household survey in Hubei Province, China, this study found that 59.18% of the sample rice farmers used a mix of biopesticides and chemical pesticides. There is mainly a complementarity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…For example, it has been shown that farmers make decisions by pursuing multiple production purposes, e.g. use biopesticides to ensure food safety for consumption and chemical pesticides to reduce costs for profitability, 64 or by showing strong motivations beyond the economic benefit, e.g. adopt biological control for reasons of health maintenance and environmental protection 65 …”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been shown that farmers make decisions by pursuing multiple production purposes, e.g. use biopesticides to ensure food safety for consumption and chemical pesticides to reduce costs for profitability, 64 or by showing strong motivations beyond the economic benefit, e.g. adopt biological control for reasons of health maintenance and environmental protection 65 …”
Section: Discussionmentioning
confidence: 99%
“…Most plants produce abundant allelopathic compounds that can effectively suppress weed seed germination and growth, minimizing the use of synthetic herbicides. [5,6] Brassicaceae, known as the cabbage or mustard family, is a group of plants with strong allelopathy. [7] The allelopathic effects of these plants have long been reported; in 1985, Willis showed that cabbage inhibits grape growth.…”
Section: Introductionmentioning
confidence: 99%
“…Pesticide application has played a positive role in controlling crop diseases and pests and in increasing crop yield. [1][2][3] For example, the global grain loss recovered by pesticide application accounted for 15% of the total grain output. 4 However, pesticides function as a double-edged sword.…”
Section: Introductionmentioning
confidence: 99%
“…Due to changes in climate and cultivation patterns, crop diseases and insect pests have intensified a trend of frequent and repetitive occurrences, posing a great threat to agricultural production and food security. Pesticide application has played a positive role in controlling crop diseases and pests and in increasing crop yield 1–3 . For example, the global grain loss recovered by pesticide application accounted for 15% of the total grain output 4 .…”
Section: Introductionmentioning
confidence: 99%